EXPLORING THE INTERSECTIONS OF TOURISM, CULTURE, AND ANTHROPOLOGY IN MOROCCO - Yahyaoui, Ahmed; Riadi, Hassane (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2024)
This study investigates the complex interplay between tourism, culture, and anthropology in Morocco, a country characterized by its rich cultural heritage and diverse landscapes. As a popular tourist destination, Morocco attracts millions of visitors each year, drawn by its historical sites, vibrant traditions, and unique gastronomy. However, the rapid growth of tourism in the region raises critical questions about cultural preservation, community involvement, and sustainable practices. Employing a qualitative research approach based on literature review and ethnographic observations, this study analyzes how tourism influences local cultures and highlights the role of anthropology in understanding these dynamics. The findings suggest that while tourism can be a catalyst for economic development, it also poses risks to cultural authenticity and social cohesion. By integrating anthropological insights, the research underscores the importance of adopting sustainable tourism practices that align with the values and traditions of Moroccan communities. Ultimately, this study contributes to a broader understanding of how tourism can coexist with cultural integrity and anthropological advocacy, offering implications for policymakers and stakeholders in Morocco's tourism sector.Tourism